Contributing Factors of Boro-Rice Production in Hakaluki Haor of Bangladesh - Alam, Masud; Sarker, Bishwajit; Uddin, Islam; Ahmed, Ashfaq (International Journal of Sustainable Agricultural Research, 2020)
Bangladesh is a riverside country and Hakaluki haor is one of the major wetlands. This research aims to identify the key factors affecting Boro-rice production and also to discover the optimum farming system. Information was collected from 150 respondents through a structured questionnaire and also focus group discussion. Descriptive analysis and factor analysis was applied to identify the key factors of Boro-rice production. Among the problems of Boro-rice production, more than two-thirds of the farmer tackled irrigation-related problems whereas insect and disease problems affect all farmland. The price of inorganic fertilizer is high but two-third of them applies inorganic fertilizer. The rate of applying high yield variety (HYV) was found very low. A remarkable portion of the farmer practices mass media so information should be strengthening for increasing production. The rate of adoption method of modern technology (i.e., crop rotation and practice intercropping) is very poor. The agricultural extension service was not sufficient. More than half of the farmers sell their production in the crisis period. Flash flood was the major natural disaster and most of the farmers claimed that heavy rain and an unexpected misplaced dam was the prime reason for flashflood. In factor analysis, seed plant cost, plow cost, irrigation cost, as well as family size and cultivable lands (last year), were found as significant factors for Boro-rice production. So, the government may give more support to the farmers so that they increase cultivable land as well as sustain their livelihood.